The Effectiveness of Medical Podcasts in Raising Women’s Health Awareness - P. Khairat (Клиническая и специальная психология)
The aim of the study was to evaluate the effectiveness of medical podcast as a novel learning tool for developing Egyptian women’s health awareness. 50 female university students were invited to participate in the study using social media advertisements. Online pretests and posttests, one based on a podcast episode regarding vaginal infections, were used to assess changes in knowledge level pre– and post–podcast listening. A second posttest was sent out 2 weeks after the first to assess knowledge retention. Results were analyzed using paired t-tests comparing mean scores before and after podcast. The results showed that the average test score increased by 62% (p<0.05). Furthermore, in both groups, there was no significant difference between average scores for posttest 1 versus posttest 2 written 2 weeks later suggested excellent knowledge retention. Podcast increased knowledge on gynecological diseases and is an effective learning tool for health care trainees in women's health. This study emphasizes the role of podcasts as a valuable educational resource within the society. The success of such initiatives will hopefully bolster the effort to correct the lack of provider knowledge in many diseases.